Polycarbonate dimer acid dihydric alcohol as well as preparation method and application thereof
By using a specific ratio of polycarbonate dimer acid diol and supported catalyst, the problem of balancing hydrolysis resistance and flexibility in moisture-curing polyurethane hot melt adhesives has been solved, achieving an efficient and environmentally friendly synthesis process and improving the stability and reliability of the material.
Patent Information
- Application Number
- CN202511372236.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-24
- Publication Date
- 2025-12-16
AI Technical Summary
Existing moisture-curing polyurethane hot melt adhesives suffer from problems such as difficulty in achieving both hydrolysis resistance and flexibility during synthesis, low catalytic system efficiency, and insufficient environmental friendliness.
Using a specific ratio of polycarbonate dimer acid diol and supported catalyst, a gradient distribution structure with dense carbonate bonds at both ends and sparse bonds in the middle of the molecular chain is formed through a two-stage process of prepolymerization-solid-phase polymerization. The composite catalytic system of [BMIM][PF6]/La(acac)3/p-toluenesulfonic acid supported by NH2-SBA-15 mesoporous molecular sieve is used.
This achievement synergistically enhances the material's high hydrolysis resistance and flexibility, increases catalyst recovery rate to over 92%, maintains catalytic activity at over 90%, and significantly reduces production costs and environmental burden.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a polycarbonate dimer acid diol, its preparation method and application, belonging to the field of hot melt adhesive technology. Background Technology
[0002] Moisture-curing polyurethane hot melt adhesive (PUR) is an adhesive that combines environmental protection with excellent performance. It has a solid content of 100% and is solvent-free. It features high initial bond strength and continuous improvement in bond performance as the curing time increases. As a result, it is widely used in many fields such as electronics, packaging, automobiles, and bookbinding, and is considered one of the most promising adhesive varieties.
[0003] In the synthesis of moisture-curing polyurethane hot melt adhesives, polyester polyols are key components that directly affect the mechanical and adhesive properties of the material. In existing technologies, dimer acid diols are typically used to improve the elongation of the material, or polycarbonate diols are used to improve resistance to damp heat. However, the ester bonds in the dimer acid diol molecular chain are easily eroded by moisture, resulting in insufficient hydrolysis resistance; while polycarbonate diols, due to their rigid cyclic structure, often lead to a significant decrease in the material's flexibility.
[0004] To address these issues, existing technologies have proposed various improvement schemes. For example, the melt transesterification method can be used to directly synthesize dimer acid polycarbonate diols. However, due to the uniform distribution of carbonate bonds in the molecular chain, the material properties exhibit a "rigid-flexible separation" phenomenon: when the carbonate content is high, the material's flexibility decreases sharply; while when the carbonate content is low, the improvement in hydrolysis resistance is limited. Furthermore, although traditional block copolymerization can introduce polycarbonate segments, poor interfacial compatibility leads to easy phase separation, resulting in large fluctuations in mechanical properties, such as a standard deviation of tensile strength exceeding 15%.
[0005] In terms of catalytic systems, existing technologies generally employ homogeneous catalysts, such as ionic liquids ([BMIM][BF4]) or metal complexes. However, these catalysts suffer from separation difficulties, with recovery rates typically below 70%, and the active components are easily lost; after three reuses, the catalytic efficiency can decrease by up to 40%. Furthermore, a large amount of solvent (accounting for more than 30% of the system) needs to be added during the reaction, which not only increases production costs but also brings significant environmental pressure.
[0006] In summary, the synthesis of moisture-curing polyurethane hot melt adhesives in the existing technology still faces problems such as difficulty in balancing hydrolysis resistance and flexibility, low efficiency of the catalytic system, and insufficient environmental friendliness. There is an urgent need to develop a polyurethane hot melt adhesive system that combines excellent comprehensive performance and a green synthesis process. Summary of the Invention
[0007] In view of the above-mentioned technical problems in the prior art, the present invention provides a polycarbonate dimer acid diol, its preparation method and application.
[0008] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: One of the objectives of this invention is to provide a polycarbonate dimer diol, wherein the number of carbonate bonds at both ends of its molecular chain is higher than the number of carbonate bonds in the middle of its molecular chain. By weight, it comprises the following raw materials: Castor oil dimer acid 90-100 parts; 50-60 parts of compounded polycarbonate monomer; 1-2 parts of supported catalyst; Antioxidant A 0.08–0.25 parts; Its number-average molecular weight (Mn) is 2500 g / mol to 3000 g / mol, its hydroxyl value is 56 mg KOH / g to 62 mg KOH / g, and its bio-based carbon content is ≥85%.
[0009] The beneficial effects of this invention are as follows: Through a specific raw material ratio, the molecular chain structure of the polycarbonate dimer acid diol is optimized, with a higher concentration of carbonate bonds at both ends of the molecular chain and a relatively lower concentration in the middle, forming a gradient distribution of "dense at both ends and sparse in the middle." This special structure allows the material to maintain high hydrolysis resistance while also possessing good flexibility, achieving a "rigid-flexible synergy." Compared to traditional materials, the polycarbonate dimer acid diol of this invention exhibits more balanced mechanical properties, with an elongation at break >600%, hydrolysis resistance retention >90%, and a significantly reduced standard deviation of tensile strength, thus improving the material's stability and reliability. The polycarbonate dimer acid diol of this invention can be widely used in the synthesis of moisture-curing polyurethane hot melt adhesives. Compared to traditional polyester polyols, the polycarbonate dimer acid diol of this invention can significantly improve the hydrolysis resistance and flexibility of hot melt adhesives, enabling them to exhibit superior performance in various application fields.
[0010] Based on the above technical solution, the present invention can also be improved as follows: Furthermore, the compounded polycarbonate monomer is composed of diphenyl carbonate and isosorbide carbonate, and the mass ratio of diphenyl carbonate to isosorbide carbonate is 2 to 4:1.
[0011] Furthermore, the supported catalyst is a composite system of [BMIM][PF6] / La(acac)3 / p-toluenesulfonic acid supported on NH2-SBA-15 mesoporous molecular sieve, with a loading of 15wt% to 25wt%.
[0012] The supported catalytic system of this invention utilizes an amino-functionalized mesoporous molecular sieve (NH2-SBA-15) as a support and loads a ternary catalyst consisting of an ionic liquid / metal complex / organic acid. A covalent bond immobilization strategy is employed to achieve highly efficient and stable loading of the active component, thereby significantly improving the recovery rate and reusability of the catalytic system. Compared to traditional homogeneous catalysts, the supported catalyst of this invention achieves a recovery rate of over 92% and retains over 90% of its catalytic activity after being reused five times, effectively solving the technical challenges of difficult separation and easy loss of active components in homogeneous catalysts.
[0013] Furthermore, the supported catalytic system of this invention fully utilizes the confinement effect of mesoporous molecular sieves. By precisely controlling the spatial distribution of active sites, it effectively suppresses the occurrence of side reactions, keeping the double bond oxidation rate below 5%, thereby further improving the selectivity of the reaction and the purity of the product. This not only significantly improves the catalytic efficiency but also reduces production costs and environmental burden, providing a feasible technical approach for the efficient and green synthesis of moisture-curing polyurethane hot melt adhesives.
[0014] Furthermore, the preparation steps of the supported catalyst include: Step a: Aminofunctionalize SBA-15 mesoporous molecular sieve to obtain NH2-SBA-15; Step b: Dissolve [BMIM][PF6], La(acac)3 and p-toluenesulfonic acid in a solvent at a mass ratio of 4-6:1-3:0.5-1.5, add NH2-SBA-15, stir at 50℃-70℃ for 3-5 hours, vacuum dry, and then calcine at 250℃-350℃ for 1-3 hours.
[0015] The supported catalyst used in this invention exhibits high catalytic efficiency and good recyclability, solving the problems of difficult catalyst separation, easy loss of active components, and low recovery rate in existing technologies. This invention, through the use of a supported catalyst, not only improves production efficiency but also reduces production costs, while simultaneously reducing solvent usage, thus meeting environmental protection requirements.
[0016] Furthermore, the castor oil dimer acid has an acid value of 185 mg KOH / g to 190 mg KOH / g and a water content of ≤0.1%.
[0017] Furthermore, the antioxidant is a hindered phenolic antioxidant, preferably Irganox 1010.
[0018] A second objective of this invention is to provide a method for preparing the above-mentioned polycarbonate dimeric acid diol, comprising the following steps: S1. Castor oil dimer acid, compound polycarbon monomer, supported composite catalyst and antioxidant are added to the reactor and prepolymerized under nitrogen protection to generate oligomers. S2. The oligomer is subjected to a solid-state polymerization reaction. By pulsed decompression and gradient heating, the carbonate segments are distributed in a gradient within the molecular chain to obtain polycarbonate dimer diol.
[0019] The beneficial effects of this invention are: This invention employs a two-stage process of prepolymerization and solid-state polymerization, combined with a pulsed decompression and gradient heating process, to achieve a gradient distribution of carbonate segments within the molecular chain, resulting in a structural characteristic of "dense at both ends and sparse in the middle." This structural design effectively improves the rigidity of the polycarbonate segments through the flexibility of the long-chain dimer segments, while significantly enhancing the overall hydrolysis resistance of the material through the densely arranged carbonate bonds at both ends. This achieves a "rigid-flexible synergy" effect, giving the material both excellent flexibility (elongation at break > 600%) and outstanding hydrolysis resistance (hydrolysis retention rate > 90%).
[0020] Specifically, regarding hydrolysis resistance, this invention constructs an effective "hydrolysis barrier" by forming dense carbonate bonds at both ends of the molecular chain. This allows the material to retain over 90% of its tensile strength after 7 days of aging under dual 85 conditions (85°C, 85% relative humidity), an improvement of over 20% compared to traditional dimer acid-based diol materials (tensile strength retention <70%). In terms of flexibility, the long-chain dimer acid structure introduced in the middle of the molecular chain enables the material to achieve an elongation at break exceeding 600%, significantly better than traditional polycarbonate diol materials (elongation at break <400%), fully meeting the application requirements of complex deformation scenarios.
[0021] Furthermore, the supported catalyst used in this invention immobilizes the active component through covalent bonds, achieving not only highly efficient catalyst recovery (single-cycle recovery rate ≥92%), but also a catalytic activity decrease of only 10% after five reuses, significantly reducing catalyst usage costs (by up to 30%) compared to traditional homogeneous catalytic systems. This technical solution improves material performance while optimizing the economics and sustainability of the production process.
[0022] Furthermore, in step S1, the conditions for the prepolymerization reaction are: temperature of 150℃~170℃, stirring speed of 200rpm~300rpm, reaction at normal pressure for 1 hour~3 hours, and the number average molecular weight of the oligomer is 800g / mol~1000g / mol.
[0023] Furthermore, the conditions for the solid-phase polymerization reaction are as follows: the pulsed vacuum level is alternately switched between -0.08MPa and -0.1MPa, with a switching cycle of 20 minutes to 40 minutes.
[0024] This invention employs a pulsed vacuum reduction process to precisely control the removal rhythm of byproducts: when the system vacuum level switches to -0.1 MPa (higher vacuum), the strong vacuum force rapidly extracts the byproducts generated in the reaction system, thereby freeing up "reaction vacancies" for the active hydroxyl groups at both ends of the molecular chain, promoting preferential reaction between the carbonate monomers and the chain ends; when the vacuum level switches to -0.08 MPa (lower vacuum), unreacted polycarbonate monomers are effectively prevented from being excessively extracted, reducing their contact and reaction probability with the hydroxyl groups in the middle of the molecular chain, ultimately forming a gradient distribution morphology of "dense carbonate bonds at both ends and relatively sparse carbonate bonds in the middle" in the molecular chain structure. This structure achieves a synergistic improvement in hydrolysis resistance (due to the dense carbonate bonds at the chain ends) and flexibility (contributed by the dimer acid segments in the middle), comprehensively optimizing the material's performance.
[0025] Furthermore, the gradient heating process of the solid-state polymerization reaction is as follows: in the first stage, the temperature is raised from 120°C to 160°C at a heating rate of 7°C / min to 9°C / min; in the second stage, the temperature is raised from 160°C to 200°C at a heating rate of 1°C / min to 3°C / min, with a total heating time of 20 to 40 minutes. Then, the temperature is maintained at 200°C for 4 hours. A constant pressure screw vacuum pump is used to ensure that the vacuum fluctuation of the reactor is maintained at ±0.005MPa, except during vacuum degree switching.
[0026] In the gradient heating process of this invention, the faster heating rate in the first stage helps to promote the rapid extension of oligomer molecular chains, while the slower heating in the second stage effectively suppresses side reactions caused by local overheating. Combined with the stable high vacuum environment throughout the process, the controllability of the reaction process is ensured, which is beneficial to improving the uniformity of molecular weight distribution and overall performance of the polymer product.
[0027] Furthermore, it also includes post-processing step S3, which includes: dissolving the product of step S2 in dichloromethane, filtering to recover the catalyst, precipitating the filtrate with ethanol, and vacuum drying.
[0028] A third objective of this invention is to provide a moisture-curing hot melt adhesive, comprising the following components by mass fraction: The above-mentioned polycarbonate dimer diols comprise 30% to 50%; Polyether polyols 10%–25%; Antioxidant B 0.1%–1%; Isocyanates 20%–35%; Coupling agent 1%–2%; Catalyst B 0.05%~0.1%; Additives: 0%–10%.
[0029] Furthermore, the number-average molecular weight of the polyether polyol is 1000 g / mol to 4000 g / mol.
[0030] Furthermore, the polyether polyol is selected from one or a combination of two or more of polypropylene glycol, polyethylene glycol and polytetrahydrofuran ether glycol, preferably Dow Chemical's PPG2000.
[0031] Furthermore, the antioxidant B is pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), preferably antioxidant 1010.
[0032] Furthermore, the isocyanate is one or a combination of two or more of toluene diisocyanate, diphenylmethane diisocyanate and hexamethylene diisocyanate, preferably Wanhua Chemical's diphenylmethane diisocyanate, brand name MDI100.
[0033] Furthermore, the coupling agent is one of KH-550, KH-560, and KH570, preferably KH550.
[0034] Furthermore, the catalyst B is one or a combination of two or more of lead octanoate, triethylamine, triethylenediamine, cobalt octanoate, zinc naphthenate, tetraisobutyl titanate, or dimorpholino diethyl ether, preferably Huntsman's dimorpholino diethyl ether, brand name DMDEE.
[0035] Furthermore, the additives include one or a combination of two or more of the following: stabilizers, diluents, fillers, and pigments.
[0036] The fourth objective of this invention is to provide a method for preparing the moisture-curing hot melt adhesive as described above, specifically including the following steps: Step A: Weigh each component, add the polycarbonate dimer acid diol, polyether polyol, and antioxidant B into the reaction vessel and stir to mix, heat to 130℃~150℃, and dehydrate under vacuum. Step B: Cool the material in the above reaction vessel to 70℃~90℃, add the melted isocyanate under stirring, and simultaneously turn on the heater to raise the temperature to 110℃~130℃. Under vacuum conditions, keep stirring for 1 hour to 2 hours. Step C: Add coupling agent and stir under vacuum for 40 minutes to 1 hour; Step D: Add the catalyst and stir under vacuum for 10 to 20 minutes. Step E: Under nitrogen protection, the material is quickly discharged and sealed in an aluminum foil bag, and cured in an oven at 70℃~90℃ to obtain the moisture-curing hot melt adhesive. Detailed Implementation
[0037] The principles and features of the present invention are described below. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.
[0038] Example 1 Preparation of gradient structure polycarbonate dimeric acid diol 1. Raw material preparation Table 1 Raw Material Information Table for Example 1
[0039] 2. Reaction steps 1) Prepolymerization stage: The above raw materials were added to a 250 mL reactor, replaced with N2 three times, and stirred at 200 rpm to raise the temperature to 160 °C. After reacting at atmospheric pressure for 2 hours, the system changed from turbid to transparent. The oligomer Mn was measured to be 950 g / mol by GPC.
[0040] 2) Solid-state polymerization stage: Cool down to 120℃, start pulse decompression (alternating between -0.08MPa and -0.1MPa, cycle 30min), then increase the temperature to 200℃ at 5℃ / min and maintain for 4 hours, keeping the vacuum level of the reactor fluctuating within ±0.005MPa.
[0041] 3) Post-processing: The product was dissolved in 50 mL of dichloromethane, the catalyst was recovered by filtration, the filtrate was poured into 200 mL of ethanol to precipitate, and after filtration, it was dried under vacuum at 60 °C for 12 hours to obtain a white waxy solid, namely polycarbonate dimer acid diol.
[0042] 3. Product performance testing The reaction products were subjected to the following performance tests, and the results are shown in Table 2.
[0043] Table 2 Performance Test Results
[0044] Example 2 1. Raw materials and processes The raw materials and dosages are the same as in Example 1, and will not be repeated here. The difference is that this example uses a supported catalyst that has been recovered 5 times (0.1% fresh catalyst is added after each recovery).
[0045] Recovery steps: After the reaction, the solution dissolved in dichloromethane was centrifuged (10,000 rpm, 15 min), the precipitate was washed three times with ethanol, dried under vacuum at 60°C for 4 hours, and calcined under nitrogen at 120°C for 2 hours.
[0046] 2. Comparison of key parameters The results of comparing the fresh supported catalyst with the supported catalyst after five recycling cycles according to this example are shown in Table 3.
[0047] Table 3 Comparison of Catalyst Parameters
[0048] Comparative Example 1 1. Raw materials and processes Catalyst: [BMIM][BF4] / La(acac)3 (mass ratio 5:2), without support, 1.56 g. Other raw materials and amounts are the same as in Example 1, and will not be repeated here.
[0049] Process: The entire process is carried out at a constant temperature of 180℃ for 6 hours. The product is dissolved in 50 mL of dichloromethane, and the catalyst is recovered by filtration (recovery rate 93%). The filtrate is poured into 200 mL of ethanol to precipitate the product. After filtration, the product is dried under vacuum at 60℃ for 12 hours to obtain a white waxy solid, namely polycarbonate dimer acid diol.
[0050] 2. Performance Comparison The reaction product of Comparative Example 1 was subjected to the following performance tests, and the results are shown in Table 4.
[0051] Table 4. Performance Test Table of Comparative Example 1
[0052] As can be seen from the results in Table 4 above, the reaction product of Comparative Example 1 showed a significant decrease in catalyst recovery rate compared to Example 1, decreasing by 28%, indicating that the unsupported catalyst has a significant disadvantage in recovery efficiency. The polydispersity index (PDI) of the product of Comparative Example 1 increased to 1.8, an increase of 50% compared to Example 1, meaning that the molecular weight distribution of the product is wider, which may affect the uniformity and performance stability of the material. In summary, the supported catalyst and the method for preparing the gradient structure polycarbonate dimer glycol of the present invention show significant advantages in improving catalyst recovery rate and optimizing product molecular weight distribution.
[0053] Comparative Example 2 1. Process Adjustment The raw materials and amounts used in this comparative example are the same as those in Example 1. The difference is that the preparation process of this comparative example involves directly heating the temperature to 200°C after prepolymerization and reacting at atmospheric pressure for 4 hours, without pulsed decompression or gradient heating.
[0054] 2. Structure and Performance The performance and structure comparison between Example 1 and Comparative Example 2 (process without pulse decompression and gradient heating) are shown in Table 5 below.
[0055] Table 5. Structural and performance data of Example 1 and Comparative Example 2
[0056] Example 3 The polycarbonate dimer acid diol prepared in Example 1 was applied to a moisture-curing polyurethane hot melt adhesive.
[0057] 1) Prepare raw materials according to the following components and mass proportions: 35 parts of polycarbonate dimer acid diol prepared in Example 1; 15 parts of polyether polyol (PPG2000); Antioxidant (1010) 0.5 parts; Isocyanate (MDI100) 22 parts; 1.5 parts of silane coupling agent (KH550); Catalyst (DMDEE) 0.05 parts.
[0058] 2) Weigh each component according to the weight proportions, add polycarbonate dimer acid diol, polyether polyol and antioxidant into the reaction vessel and stir to mix, heat to 140℃, draw vacuum, and dehydrate for 2.5h under vacuum degree ≤-0.095 MPa; 3) Cool the material in the above reaction vessel to 80°C, add the melted isocyanate while dispersing at 500 RPM, and simultaneously turn on the heater to raise the temperature to 120°C and maintain a vacuum of ≤-0.095 MPa while stirring at high speed at 120°C for 1.5 hours. 4) Add silane coupling agent and stir for 45 min under a vacuum of ≤-0.095 MPa; 5) Add the catalyst and stir for 15 min under a vacuum of ≤-0.095 MPa; 6) The material is rapidly discharged under nitrogen protection and sealed in an aluminum foil bag, then cured in an oven at 85°C to obtain the moisture-curing polyurethane hot melt adhesive.
[0059] Comparative Example 3 1) Prepare raw materials according to the following components and mass proportions: Dimer acid diol (SP-3190) 35 parts; 15 parts of polyether polyol (PPG2000); Antioxidant (1010) 0.5 parts; Isocyanate (MDI100) 25 parts; Coupling agent (KH550) 1.5 parts; Catalyst (DMDEE) 0.05 parts.
[0060] 2) Weigh each component according to the weight proportions, add dimer acid diol SP-3190, polyether polyol and antioxidant into the reaction vessel and stir to mix, heat to 140℃, draw vacuum, and dehydrate for 2.5h under vacuum degree ≤-0.095 MPa conditions; 3) Cool the material in the above reaction vessel to 80°C, add the melted isocyanate while dispersing at 500 RPM, and simultaneously turn on the heater to raise the temperature to 120°C and maintain a vacuum of ≤-0.095 MPa while stirring at high speed at 120°C for 1.5 hours. 4) Add silane coupling agent and stir for 45 min under a vacuum of ≤-0.095 MPa; 5) Add the catalyst and stir for 15 min under a vacuum of ≤-0.095 MPa; 6) The material is rapidly discharged under nitrogen protection and sealed in an aluminum foil bag, then cured in an oven at 85°C to obtain the moisture-curing polyurethane hot melt adhesive.
[0061] Comparative Example 4 1) Prepare raw materials according to the following components and mass proportions: Polycarbonate diol (Dornex G3452) 35 parts; 15 parts of polyether polyol (PPG2000); Antioxidant (1010) 0.5 parts; Isocyanate (MDI100) 25 parts; 1.5 parts of silane coupling agent (KD550); Catalyst (DMDEE) 0.05 parts.
[0062] 2) Weigh each component according to the weight proportions, add polycarbonate diol G3452, polyether polyol and antioxidant into the reaction vessel and stir to mix, heat to 140℃, draw vacuum, and dehydrate for 2.5h under vacuum degree ≤-0.095 MPa. 3) Cool the material in the above reaction vessel to 80°C, add the melted isocyanate while dispersing at 500 RPM, and simultaneously turn on the heater to raise the temperature to 120°C and maintain a vacuum of ≤-0.095 MPa while stirring at high speed at 120°C for 1.5 hours. 4) Add silane coupling agent and stir for 45 min under a vacuum of ≤-0.095 MPa; 5) Add the catalyst and stir for 15 min under a vacuum of ≤-0.095 MPa; 6) The material is rapidly discharged under nitrogen protection and sealed in an aluminum foil bag, then cured in an oven at 85°C to obtain the moisture-curing polyurethane hot melt adhesive.
[0063] The polyurethane hot melt adhesives of Example 3 and Comparative Examples 3 and 4 were subjected to the following tests: 1. Adhesive strength: The adhesive performance of the hot melt adhesive was tested according to the national standard GB / T5210-2006 "Paints and Varnishes - Pull-off Adhesion Test", using PC as the adhesive material and a bonding dimension of 30mm. 2 The adhesive layer thickness is 0.18mm~0.22mm, and the amount of adhesive is about 8mg. After the overlapped sample is cured in a constant temperature and humidity chamber at 25℃ and 50%Rh for 7 days, the pull-out strength is tested using a universal tensile testing machine.
[0064] 2. Hydrolysis resistance: The above-mentioned bonding strength samples were placed in a 25℃, 50%Rh constant temperature and humidity chamber for 7 days to cure, and then placed in a double 85 environmental chamber for 10 days. After 10 days, the bonding strength of the samples was tested according to the above method, and the bonding strength decay was tested.
[0065] 3. Elongation at break and tensile strength test: The elongation at break of the hot melt adhesive is tested according to the national standard GB / T528-2009 "Standard for determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber". The standard sample is prepared and cured in a constant temperature and humidity chamber at 25℃ and 50%Rh for 7 days. Then, the elongation at break and tensile strength are tested using a universal tensile testing machine.
[0066] 4. Place the above-mentioned bonding strength samples in a 25℃, 50%Rh constant temperature and humidity chamber for 7 days to cure, and then place them in a double 85 environmental chamber for 10 days. After 10 days, test the tensile strength decay of the samples according to the above method.
[0067] The performance test results of Example 3 and Comparative Examples 3 and 4 are shown in Table 6 below: Table 6 Performance test results of polyurethane hot melt adhesive
[0068] As can be seen from the data in Tables 3 and 4, the present invention uses a supported catalyst and, through optimized support design and active component immobilization strategy, significantly improves the catalyst recovery performance, achieves efficient recycling, and effectively solves the technical bottleneck of difficult or impossible catalyst recovery in traditional catalytic systems.
[0069] As can be seen from the data comparison of Example 1 and Comparative Examples 1-2, the supported catalyst of the present invention not only significantly improves the catalyst recovery rate, but also, in combination with specific process control, can effectively narrow the molecular weight distribution of the product, improve the product uniformity, and significantly reduce the yellowing phenomenon during the synthesis process, thereby improving the color quality and performance stability of the product.
[0070] The data from Examples 3 and Comparative Examples 3-4 show that the polycarbonate dimer acid diol with a gradient structure proposed in this invention exhibits superior overall performance compared to traditional dimer acid diols and polycarbonate diols. Experimental results demonstrate that this material not only possesses higher initial bond strength and elongation at break, but also maintains high strength retention and flexibility under high-temperature and high-humidity aging conditions, exhibiting outstanding aging resistance and long-term stability. This technical solution successfully overcomes the problem of traditional materials struggling to balance hydrolysis resistance and flexibility, providing a new technical approach for the development of high-performance polyurethane materials.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A polycarbonate dimer acid diol, characterized in that, The number of carbonate bonds at both ends of its molecular chain is greater than the number of carbonate bonds in the middle of its molecular chain; By weight, it comprises the following raw materials: Castor oil dimer acid 90-100 parts; 50-60 parts of compounded polycarbonate monomer; 1-2 parts of supported catalyst; Antioxidant A 0.08-0.25 parts.
2. The polycarbonate dimer diol according to claim 1, characterized in that, The compounded polycarbonate monomer is composed of diphenyl carbonate and isosorbide carbonate, and the mass ratio of diphenyl carbonate to isosorbide carbonate is 2 to 4:
1.
3. The polycarbonate dimer diol according to claim 1, characterized in that, The supported catalyst is a composite system of [BMIM][PF6] / La(acac)3 / p-toluenesulfonic acid supported on NH2-SBA-15 mesoporous molecular sieve, with a loading of 15wt% to 25wt%.
4. The polycarbonate dimer diol according to claim 3, characterized in that, The preparation steps of the supported catalyst include: Step a: Aminofunctionalize SBA-15 mesoporous molecular sieve to obtain NH2-SBA-15; Step b: Dissolve [BMIM][PF6], La(acac)3 and p-toluenesulfonic acid in a solvent at a mass ratio of 4-6:1-3:0.5-1.5, add NH2-SBA-15, stir at 50℃-70℃ for 3-5 hours, vacuum dry, and then calcine at 250℃-350℃ for 1-3 hours.
5. The polycarbonate dimer diol according to claim 1, characterized in that, The castor oil dimer has an acid value of 185 mg KOH / g to 190 mg KOH / g and a water content of ≤0.1%; the antioxidant is a hindered phenolic antioxidant.
6. A method for preparing polycarbonate dimeric acid diol according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Castor oil dimer acid, compound polycarbon monomer, supported composite catalyst and antioxidant are added to the reactor and prepolymerized under nitrogen protection to generate oligomers. S2. The oligomer is subjected to a solid-state polymerization reaction. By pulsed decompression and gradient heating, the carbonate segments are distributed in a gradient within the molecular chain to obtain polycarbonate dimer diol.
7. The method for preparing polycarbonate dimeric acid diol according to claim 6, characterized in that, In step S1, the prepolymerization reaction conditions are: temperature of 150℃~170℃, stirring speed of 200rpm~300rpm, reaction at normal pressure for 1 hour~3 hours, and the number average molecular weight of the oligomer is 800g / mol~1000g / mol.
8. The method for preparing polycarbonate dimeric acid diol according to claim 6, characterized in that, In step S2, the conditions for the solid-phase polymerization reaction are: The pulsed vacuum level alternates between -0.08MPa and -0.1MPa, with a switching cycle of 20 to 40 minutes. The gradient heating process is as follows: in the first stage, the temperature is raised from 120℃ to 160℃ at a heating rate of 87℃ / min to 9℃ / min; in the second stage, the temperature is raised from 160℃ to 200℃ at a heating rate of 1℃ / min to 3℃ / min. The total heating time is 20 minutes to 40 minutes. Then, the temperature is maintained at 200℃ for 4 hours, and the vacuum degree of the reactor is maintained at ±0.005MPa.
9. A moisture-curing hot melt adhesive, characterized in that, By mass fraction, it includes the following components: Polycarbonate dimer glycol 30%–50%; Polyether polyols 10%–25%; Antioxidant B 0.1%–1%; Isocyanates 20%–35%; Coupling agent 1%–2%; Catalyst B 0.05%~0.1%; Additives 0%–10%; The polycarbonate dimer acid diol is the polycarbonate dimer acid diol as described in any one of claims 1 to 5 or the polycarbonate dimer acid diol prepared by the preparation method described in any one of claims 6 to 8.
10. A method for preparing a moisture-curing hot melt adhesive as described in claim 9, characterized in that, Specifically, the following steps are included: Step A: Weigh each component, add the polycarbonate dimer acid diol, polyether polyol, and antioxidant B into the reaction vessel and stir to mix, heat to 130℃~150℃, and dehydrate under vacuum. Step B: Cool the material in the above reaction vessel to 70℃~90℃, add the melted isocyanate under stirring, and simultaneously turn on the heater to raise the temperature to 110℃~130℃. Under vacuum conditions, keep stirring for 1 hour to 2 hours. Step C: Add coupling agent and stir under vacuum for 40 minutes to 1 hour; Step D: Add the catalyst and stir under vacuum for 10 to 20 minutes. Step E: Under nitrogen protection, the material is quickly discharged and sealed in an aluminum foil bag, and cured in an oven at 70℃~90℃ to obtain the moisture-curing hot melt adhesive.